Impact of Kawasaki disease on juvenile idiopathic arthritis in real-world patients: A population-based cohort study - Liao, Li-Chin; Fu, Yi-Hsiu; Chuang, Chieh-Mao; Liao, Pei-Lun; Wei, James Cheng-Chung; Fu, Yun-Ching (Frontiers in Immunology, 2022)
Objectives Recent research has demonstrated the commonality of several biological markers between Kawasaki disease and juvenile idiopathic arthritis (JIA), including interleukin-1β and -6. Therefore, in this cohort study, we assessed whether Kawasaki disease increases the risk of JIA. Methods This study enrolled 7009 patients with and 56 072 individuals without Kawasaki disease in the period 2010–2018 from Taiwan’s National Health Insurance Research Database. On the basis of sex, age, and comorbidities, we executed propensity score matching at the ratio 1:8. The adjusted hazard ratio (aHR) for JIA was determined through multiple Cox regression. Stratified analysis and sensitivity tests were also employed. Results When adjusting for age, sex, and comorbidities, the JIA risk was noted to be 2.02-fold greater in children with Kawasaki disease than it was in those without (aHR: 2.02, 95% confidence interval: 1.12–3.67, p = 0.0205). The sensitivity test and subgroup analysis obtained consistent findings in the different sex and comorbidity subgroups. Conclusion Children's risk of JIA is higher if they have Kawasaki disease. Pediatricians should consider the possibility of JIA in this population. More investigations are necessary to identify the pathological mechanisms that link JIA and Kawasaki disease.